Execution of a 15-level multilevel inverter for hybrid energy storage system (HESS)-based Electric Vehicles. Issue 3 (3rd April 2022) - Tirpude, Saket; Sawant, Sachin; Holmukhe, R. M.; Gandhar, Abhishek; Hans, Drishti; Hasarmani, T. S.
Abstract: With non-linear loads laying a siege in almost every corner of our households, harmonics are hard to mitigate. The short pulses of current drawn by such loads distort the current waveform and deteriorate the health of the electric utility and appliances. The integral multiple of the fundamental waveform's frequency i.e. the harmonics when summed up become total harmonic distortion (THD). Multilevel inverters (MLI) outshine the traditional two-level inverters because of their capability to produce reduced THD and electromagnetic interference (EMI). In this research article, an innovative 15-level inverter is realized for THD mitigation with 10 MOSFET switches to regulate high power values. The system is initially modelled on MATLAB/SIMULINK and then practically implemented which affirms a THD mitigation of 4% with swish waveform to fulfill the IEEE519.